Enzymatic Hydrolysis Of Olive Industry Solid Waste Into Glucose, The Precursor Of Bioethanol - Israa Jamal Mohammad Dagher (My University, 2015)
Jeft is a solid by-product generated during olive oil production. As a lignocellulose, jeft material is consist of cellulose, hemicellulose, lignin and other extractives. Previous research work successfully extracted about 40-45% cellulose from jeft raw materials. Jeft is considered as a biomass sources for the production of renewable energy. Our study investigated the process of hydrolyzing jeft into its monomers, glucose through the a two-step process that involves activation by pre-treatment of olive pulp with water, NaOH, Ca(OH)₂ and acetic acid. The activation step was followed by an enzymatic hydrolysis of cellulose to glucose. A combination of two enzymes cellulase and β-glucosidase were used in the hydrolysis. The aim of this step was to convert glucose to ethanol which is used as fuel source. The highest yield of 85.02% glucose was obtained using enzyme concentration cellulose of 15.0 mg/g jeft and β-glucosidase 20.0 mg/g jeft at 45°C with 10% NaOH pre-treated jeft sample for 8 hr at pH = 4.8. Whereas a pure cellulose produces about 95.30% glucose which is considered the highest yield obtained in our project in the same condition listed above.

الجفت هو عبارة عن المادة الصلبة الناتجة عن عملية عصر الزيتون والذي يتكون بشكل اساسي من السيليلوز, شبه السيليلوز واللجنين بالاضافة الى مكونات جانبية اخرى. اشارت الابحاث السابقة الى ان الباحثون نجحوا في استخراج السيليوز بنسبة حوالي 40-45% من مادة الجفت الخام. تعتبر مادة الجفت مصدرا حيويا لانتاج الطاقة المتجددة عن طريق تحليل مادة الجفت الى مكوناتها الاساسية وهي سكريات احادية بسيطة بخطوتين وهما: 1- معالجة وتنشيط مادة الجفت وتفكيكها بواسطة الماء, هيدروكسيد الصوديوم, هيدروكسيد الكالسيوم وحمض الخليك لتسهيل عملية دخول الانزيمات في الخطوة التالية. 2- الخطوة الثانية تتضمن اختراق الانزيمات مادة السيليلوز وتحللها الى سكريات احادية بسيطة. تتكون هذه الانزيمات من انزيمين وهما سيليوليز وبيتا- جلوكوزايديز وهما المسؤولان عن تحليل مادة السليلوز الى سكريات. الهدف من عملية تحول السيليلوز الى سكر هو تحويل السكريات الاحادية الى مادة الايثانول الحيوي والذي يعتبر مصدر متجدد للطاقة بواسطة عملية التخمر. من خلال هذا البحث توصلنا الى ان اعلى نسبة سكر حصلنا عليها من الجفت الخام هي 85.02% وذلك من خلال الظروف التالية: 1- تركيز انزيم السيليوليز = 15ملغم/غم جفت و تركيز انزيم ال بيتا- جلوكوزايديز = 20ملغم/غم جفت. 2- درجة الحرارة المثلى 45 درجة مئوية. 3- الوقت 8 ساعات. 4- درجة حموضة الوسط المحيط 4.8 . في حين اظهرت الدراسة ان تحلل مادة السيليوز والمستخلصة حققت اعلى نسبة سكر والتي وصلت الى 95.30% في نفس الظروف المذكورة اعلاه.
استخدام الانزيمات في تحليل المواد الصلبة (جفت الزيتون) وتحويله الى سكر الجلوكوز، المؤدي الى تكون الايثانول الحيوي